Risk Factors of Lymph Node Metastasis and Its Prognostic Significance in Early Gastric Cancer: A Multicenter Study - Wang, Jinfeng; Wang, Liang; Li, Sha; Bai, Fei; Xie, Hailong; Shan, Hanguo; Liu, Zhuo; Ma, Tiexiang; Tang, Xiayu; Tang, Haibing; Qin, Ang; Lei, Sanlin; et al. (Frontiers in Oncology, 2021)
Background: Early gastric cancer (EGC) is invasive gastric cancer that invades no deeper than the submucosa, regardless of lymph node metastasis (LNM). It is mainly treated by surgery. Recently, the resection range of EGC has been minimized, but cancer recurrence and overall survival in some patients should be given high status. LNM is an important indicator of prognosis and treatment in gastric cancer. The law of the number and location of metastatic lymph nodes in EGC is not yet clear. Therefore, we aimed to identify the risk factors of LNM in radically resected EGC and guide treatment. Methods: The clinicopathological factors of 611 patients with EGC were retrospectively analyzed in six hospitals between January 2010 and December 2016. The relationship between clinicopathological factors and LNM, as well as their prognostic significance, were analyzed by univariate and multivariate analyses. Results: The rate of LNM was 20.0% in the 611 EGC patients. The depth of invasion, differentiation type, tumor diameter, morphological ulceration, and lymphovascular invasion were independent risk factors for LNM (P<0.05) by logistic regression analysis. Tumor location in the proximal third of the stomach and morphological ulceration were significant factors for group 2 LNM. Moreover, the 5-year survival rate was 94.9% for patients with no positive nodes, 88.5% for patients with 1-2 positive nodes, 64.3% for patients with 3-6 positive nodes, and 41.8% for patients with >6 metastatic nodes. Interestingly, the 7-year risk of relapse diminished for patients with no LNM or retrieved no less than 15 lymph nodes. Conclusions: Fifteen lymph node dissection and D2 radical operation are the surgical options in case of high risk factors for LNM. Extended lymph node dissection (D2+) is recommended for morphological ulceration or disease located in the proximal third of the stomach due to their high rate of group 2 LNM. Furthermore, LNM is a significant prognostic factor of EGC. Moreover, lymph nodes can also play a significant role in the chemotherapeutic and radiotherapy approach for non-surgical patients with EGC.